Nahdlatul Ulama Da'wah Dynamics: Socio-Cultural Change and Disruption - Siti Uswatun Khasanah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The dynamics of da'wah and social and cultural change/disruption, especially since the middle of the last century, have challenged major civic organizations such as Nahdlatul Ulama (NU). The Nahdlatul Ulama is often considered a conservative organization, unprogressive, and even often stigmatized, but this organization continues to fly its wings and capture the code of change. This study examines the dynamics of Nahdlatul Ulama's da'wah method, especially in the deal with changes and socio-cultural disruptions. This paper uses qualitative methods with a transdisciplinary approach. It consists of a sociological, historical, and cultural approach, mainly emphasizing integrating da'wah and communication science. The subjects of this study are the Chairmen at PBNU for the 2015-2020 period—data analysis in this study by data reduction, display, conclusion,  and verification. The results of this study expose: (1) The era of disruption has a tremendous impact on the da'wah method (2) Nahdlatul Ulama utilizes digital da'wah Media, such as social media (Twitter, Facebook,  Instagram, Youtube, and Google Plus), NU Online, 146 Chanel, Aswaja TV, Nutizen, Islamic.com, and Film. (3) Nahdlatul Ulama's da'wah materials contain: countering fundamentalism, radicalism, terrorism, and Wahabism by strengthening aswaja content, ukhuwah trilogy (ukhuwwah bashariyyah, ukhuwwah wathaniyyah, ukhuwwah Islamiyyah). (4) Nahdlatul Ulama continues to revive slametan, praise, tahlilan, dhikr after prayer, maulid nabi, berzanji, halal bi halal, sarong, skullcap, turban, blangkon, istighasah, recitation, pilgrimage, haul, and bahth al-masa'il.